Conformation Techniques for False Smut Pathogen (U. virens) on Rice through Cultural and Molecular Tools in Telangana - Somshetty, Ravali; Basha, S. Ameer; Pushpavalli, S. N. C. V. L.; Babu, T. Kiran; Mohan, Y. Chandra; Naik, B. Balaji (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted during period of January to April, 2022 at the Department of Plant Pathology and Institute of Biotechnology, Professor Jayashankar Telangana State Agricultural University, Rajendranagar, Hyderabad, Telangana state, India. The main objective of this study was to investigate cultural and morphological characteristics of U. virens isolates on potato sucrose medium (PSA) and their molecular confirmation collected from rice growing regions of Telangana during the kharif (rainy season), 2021. The isolates showed varying colony diameters and growth rates, with Uv3 reaching a maximum diameter of 77 mm and a growth rate of 2.85 mm, while Uv11 exhibited a minimum diameter of 40 mm with a growth rate of 1.48 mm. Notably, twenty two isolates showed diverse characteristics, including colony color, elevation, zonation, sectoring, and chlamydospore formation. Cluster analysis revealed the formation of five major groups, each group containing isolates with distinct features and PCR amplification with universal and species-specific primers yielded products of 700 bp and 380 bp, respectively. Phylogenetic tree analysis, indicated, Uv3 and Uv15 belonged to clade X and clade VII, respectively, both comprising Indian isolates. In contrast, Uv4 was grouped under clade II, which included both Chinese and Indian isolates. The proposed technique coupled with information of U. virens will immensely contribute to further studies on this fungus and false smut disease in India.